If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(-6x-6)=-6(5-9x)
We move all terms to the left:
5(-6x-6)-(-6(5-9x))=0
We add all the numbers together, and all the variables
5(-6x-6)-(-6(-9x+5))=0
We multiply parentheses
-30x-(-6(-9x+5))-30=0
We calculate terms in parentheses: -(-6(-9x+5)), so:We get rid of parentheses
-6(-9x+5)
We multiply parentheses
54x-30
Back to the equation:
-(54x-30)
-30x-54x+30-30=0
We add all the numbers together, and all the variables
-84x=0
x=0/-84
x=0
| 5x=3x*4 | | -2g+3=-13 | | 4(x-1)-2x=3x-(4+x) | | 3x+15=x+73 | | 5(x-4)-2x=3x-4 | | 2×-13=5x-1 | | 6x+5+4x=6x+5+4x | | M+2a=5a | | 8(x-17)+12=34 | | n+1=n+1 | | 9^3x-2=9^2x+1 | | 20b-2=4 | | -6(-3p+10)=-240 | | 3/2y-4=-1 | | 2x+4=2(3x-8) | | 13=5+2w | | 18+4n=2(6-n) | | 3-3b=-7b+4b+3 | | 3(3x-3)=13 | | 2.1/2(2)=x | | 3x-100=-10x+30 | | 4(1/2x-1/4)=(2x+1/2) | | 4(1+4x)=52 | | 4x-9+2x+15=180 | | x+11+5x=8x-3 | | 3y-6=48 | | x2−4=−28 | | -3+24x+22x+7=180 | | 60/3+n/3=84/5+n/5 | | 2n=2.62 | | –8−7u=–6u | | (2^5)x+15=(4^5)x-6 |